Problematiek van studentwerwing in verpleging - H. van Wyk (AOSIS, 1982)
The current manpower shortage has greatly influenced recruitment to the nursing profession. A related issue is the movement of student and qualified nurses out of the profession. Various problem areas have been identified and to improve recruitment it is imperative that: - recruitment methods be improved; - staffing policy be changed so that the student nurse is not regarded mainly as a worker; - that the status of clinical nursing, especially the status of the ward sister, be reinstated; - that more guidance and support be provided for student nurses; - that the socio-economic status of the nurse receive urgent attention. Furthermore, every nurse has an important role in recruitment and in building the image of nursing by always projecting a positive attitude towards her profession.